An efficient synthetic route to l-γ-methyleneglutamine and its amide derivatives, and their selective anticancer activity - Hossain, Md Imran (RSC Adv, 2021)
In cancer cells, glutaminolysis is the primary source of biosynthetic precursors, fueling the TCA cycle with glutamine-derived α-ketoglutarate. The enhanced production of α-ketoglutarate is critical to cancer cells as it provides carbons for the TCA cycle to produce glutathione, fatty acids, and nucleotides, and contributes nitrogens to produce hexosamines, nucleotides, and many nonessential amino acids. Efforts to inhibit glutamine metabolism in cancer using amino acid analogs have been extensive. l-γ-Methyleneglutamine was shown to be of considerable biochemical importance, playing a major role in nitrogen transport in Arachis and Amorpha plants. Herein we report for the first time an efficient synthetic route to l-γ-methyleneglutamine and its amide derivatives. Many of these l-γ-methyleneglutamic acid amides were shown to be as efficacious as tamoxifen or olaparib at arresting cell growth among MCF-7 (ER(+)/PR(+)/HER2(−)), and SK-BR-3 (ER(−)/PR(−)/HER2(+)) breast cancer cells at 24 or 72 h of treatment. Several of these compounds exerted similar efficacy to olaparib at arresting cell growth among triple-negative MDA-MB-231 breast cancer cells by 72 h of treatment. None of the compounds inhibited cell growth in benign MCF-10A breast cells. Overall, N-phenyl amides and N-benzyl amides, such as 3, 5, 9, and 10, arrested the growth of all three (MCF-7, SK-BR-3, and MDA-MB-231) cell lines for 72 h and were devoid of cytotoxicity on MCF-10A control cells; N-benzyl amides with an electron withdrawing group at the para position, such as 5 and 6, inhibited the growth of triple-negative MDA-MB-231 cells commensurate to olaparib. These compounds hold promise as novel therapeutics for the treatment of multiple breast cancer subtypes.